2019
DOI: 10.1007/s10980-019-00805-y
|View full text |Cite
|
Sign up to set email alerts
|

Fine-scale characteristics of the boundaries between annual patches and perennial patches in a meadow steppe

Abstract: Context Boundaries are ubiquitous and may have crucial influence on the pattern, process, and dynamics of landscapes. However, there is little understanding of mechanisms that govern changes in the location and composition of boundaries. Especially, it is still uncertain whether there are definite relationships between vegetation and soil. At smaller scales, investigation of more detailed soil and vegetation characteristics can more clearly reveal the linkages between soil properties and vegetation patterns. O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 58 publications
(84 reference statements)
2
7
0
Order By: Relevance
“…These results are similar to those found in previous studies of soil and vegetation indicators at the boundary (Cao et al, 2019, Maas et al, 2016. Meanwhile, the results of this study found that the changes in vegetation richness were most influenced by organic matter, and the changes in vegetation richness and organic matter were completely consistent in all types of grasslands (Figure 2A, Figure 3D).…”
Section: Spatial Pattern Of Plant Variables and Soil Characteristicssupporting
confidence: 93%
See 3 more Smart Citations
“…These results are similar to those found in previous studies of soil and vegetation indicators at the boundary (Cao et al, 2019, Maas et al, 2016. Meanwhile, the results of this study found that the changes in vegetation richness were most influenced by organic matter, and the changes in vegetation richness and organic matter were completely consistent in all types of grasslands (Figure 2A, Figure 3D).…”
Section: Spatial Pattern Of Plant Variables and Soil Characteristicssupporting
confidence: 93%
“…These patches of vegetation provide a good environment for the study of micro-scale edge effects, all biotic and abiotic factors, and the small dynamics of their relationship with the environment are highly relevant, this relationship can greatly affect the vegetated landscape in the study area, resulting in a landscape pattern that now varies in patch size. (Ferro and Morrone, 2014;Oliveras and Malhi, 2016;Cao et al, 2019). And this association will have a great impact on the vegetation landscape in the study area, resulting in the formation of the current patch size of the landscape pattern.…”
Section: Introductionmentioning
confidence: 96%
See 2 more Smart Citations
“…In contrast, we investigated much smaller-scaled boundaries on the quartz islands of our study area, where microscale soil heterogeneity reflects the spatial distribution of vegetation communities (Schmiedel et al, 2015) and seems to be the principal abiotic factor shaping diversity patterns. Studies investigating the sharp plant species turnover caused by small-scale edaphic gradients are scarce, presumably because transition types with this grain size seem to occur mainly on sites with special soils in semi-arid or arid environments such as gypsum (Rubio & Escudero, 2000) or serpentine (Harrison et al, 2006); or saline/alkaline soils in grasslands (Cao et al, 2019).…”
Section: Species Turnover Stronger Than Nestedness Componentmentioning
confidence: 99%